2014
DOI: 10.1109/tec.2014.2313642
|View full text |Cite
|
Sign up to set email alerts
|

Solar Plane Propulsion Motors With Precompressed Aluminum Stator Windings

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 9 publications
0
61
1
Order By: Relevance
“…Hence, a modular radial-flux machine topology with an openslot stator and a preformed winding construction has been selected here. The preformed and/or compressed concentrated winding topology allows for the coils to be manufactured in isolation, in a simple and repeatable manner providing improved winding performance measures and manufacturability, as compared with other winding topologies [6], [8], [9], [12], [15], [25]. The preformed coils are then placed in the stator slots with an appropriate slot liner and secured with a slot wedge.…”
Section: Design Philosophymentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a modular radial-flux machine topology with an openslot stator and a preformed winding construction has been selected here. The preformed and/or compressed concentrated winding topology allows for the coils to be manufactured in isolation, in a simple and repeatable manner providing improved winding performance measures and manufacturability, as compared with other winding topologies [6], [8], [9], [12], [15], [25]. The preformed coils are then placed in the stator slots with an appropriate slot liner and secured with a slot wedge.…”
Section: Design Philosophymentioning
confidence: 99%
“…The 'design for cost' and 'design for manufacture' paradigms have gained increasing interest, which is reflected in the available literature [1]- [12]. In particular, research into machine designs with reduced quantities of rare-earth PM materials achieved through the adoption of interior PM machine topologies or the use of alternative PM materials such as ferrites, Dysprosiumfree or Dysprosium-less NdFeB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This machine has been shown to exhibit high torque density and higher efficiency for the same 18 frame size compared to both the induction motor and the conventionally wound synchronous reluctance machine [26,27,28]. The main benefits of adopting this cSynRM topology of machine are as follows; At an initial glance, the topology appears to be very desirable, the short end winding due to their short span now contain less copper and do not overlap other phases, aiding electrical isolation and neat coils to be wound -effectively enabling higher slot fill factors, upwards 80% in some cases when compressed coils are utilized [31]. However, there are associated drawbacks of selecting this topology.…”
Section: Fig 9 Comparison Of Synrm and Csynrm Topologiesmentioning
confidence: 99%
“…A very short axial length (along shaft centre axis) of the end windings was achieved, only 19mm. A fill factor of approximately 60% was achieved, however recent work has shown that much high fills are possible [13] if the coils are precompressed. The rotor component was electro-discharge machined, a stator lamination is shown in Figure. 13.…”
Section: Prototype Machinementioning
confidence: 99%